2009
DOI: 10.1021/bi9020346
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Escherichia coli Apolipoprotein N-Acyltransferase (Lnt) Exists as an Extracytoplasmic Thioester Acyl-Enzyme Intermediate

Abstract: Escherichia coli apolipoprotein N-acyltransferase (Lnt) transfers an acyl group from sn-1-glycerolphospholipid to the free α-amino group of the N-terminal cysteine of apolipoproteins, resulting in mature triacylated lipoprotein. Here we report that the Lnt reaction proceeds through an acyl enzyme intermediate in which a palmitoyl group forms a thioester bond with the thiol of active site residue C387 that was cleaved by neutral hydroxylamine. Lnt(C387S) also formed a fatty acyl intermediate that was resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 16 publications
2
62
0
Order By: Relevance
“…Previous studies have demonstrated that mutating the active-site cysteine of Lnt to a serine leads to the formation of an acyl-enzyme intermediate that is resistant to reducing agents (25). Such mutants are also unable to efficiently resolve the acyl enzyme intermediate in the second step of N-acylation, likely owing to the substantially higher pK a of the serine side chain, which makes it a poor leaving group compared with the cysteine in the wild-type enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that mutating the active-site cysteine of Lnt to a serine leads to the formation of an acyl-enzyme intermediate that is resistant to reducing agents (25). Such mutants are also unable to efficiently resolve the acyl enzyme intermediate in the second step of N-acylation, likely owing to the substantially higher pK a of the serine side chain, which makes it a poor leaving group compared with the cysteine in the wild-type enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…4D). Additionally, it is wellestablished that W237 is essential for Lnt activity (24,25,27), although the reason behind this requirement has been elusive. Based on our structure, we therefore propose this structural element to be a potential phosphate-recognition site.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations